Bank foreign assets, government support and international spillover effects of sovereign rating events on bank stock prices - Schertler, Andrea; Moch, Nils (Journal of Banking & Finance, 2021)
We study the international spillover effects of sovereign rating events on the stock returns of large banks in nonevent countries. Using S&P rating assessments from 1983 to 2018, we find that negative sovereign rating events spill over to foreign banks’ stock returns through the foreign asset holdings channel, especially if the rating shock to domestic banks is severe. Foreign sovereign debt holdings are not the only source to open such a channel. Negative sovereign rating events also spill over through foreign interbank exposures, but not through foreign claims to nonbank firms. We further find a previously undocumented positive side effect of government support to banks. The guarantee channel limits international spillover effects if banks with strong expected government support are located in countries with high sovereign ratings.